2005
DOI: 10.1007/s00216-004-2860-2
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible channels for field-flow fractionation of biological samples: correlation between surface composition and operating performance

Abstract: Biocompatible methods capable of rapid purification and fractionation of analytes from complex natural matrices are increasingly in demand, particularly at the forefront of biotechnological applications. Field-flow fractionation is a separation technique suitable for nano-sized and micro-sized analytes among which bioanalytes are an important family. The objective of this preliminary study is to start a more general approach to field-flow fractionation for bio-samples by investigation of the correlation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
0
11
1
Order By: Relevance
“…It meant that sample loss during migration was not critical and much can be referred from during the focusing/relaxation process. While it was reported in a recent study, using a PSf HF membrane, that a quite uniform protein layer was found all along the fiber rather than in the focusing zone [18], the current study did not show the same trend according to the observed data for different lengths of HF fibers. This may originate from the difference in the hydrophobicity of membrane materials (PAN HF membrane is more hydrophobic than PSf).…”
Section: Methodscontrasting
confidence: 75%
See 1 more Smart Citation
“…It meant that sample loss during migration was not critical and much can be referred from during the focusing/relaxation process. While it was reported in a recent study, using a PSf HF membrane, that a quite uniform protein layer was found all along the fiber rather than in the focusing zone [18], the current study did not show the same trend according to the observed data for different lengths of HF fibers. This may originate from the difference in the hydrophobicity of membrane materials (PAN HF membrane is more hydrophobic than PSf).…”
Section: Methodscontrasting
confidence: 75%
“…Resolution achieved in the fractograms of Fig. 2 indicates that the HF FlFFF performance for protein samples is comparable to that which can be obtained using a conventional, flat-channel FlFFF channel [18], except the low separation speed in HF FlFFF. Since _ V V rad = 0.54 mL/min used in the case of the bottom run of Fig.…”
Section: Methodsmentioning
confidence: 50%
“…The multi-element detection, quantification, depth profiling capabilities and high binding energy resolution make it well suited to the examination of a range of both materials commonly used in bioengineering applications (e.g. glass and polystyrene), 6 novel polymer systems 7,8 as well as thin film surface modifications, 9 -13 and native and grown surface oxides.…”
Section: Characterisation Of Coatings and Surface Chemistrymentioning
confidence: 99%
“…The carrier liquid was water containing 0.1% FL-70 (Fisher Scientific, Loughborough, UK) detergent (a low-foaming; low alkalinity; and phosphate-, chromate-, silicate-free mixture of anionic and nonionic surfactants). Polystyrene (PS) latex beads of various nominal diameters (6,8,12,20, 40 µm) purchased from Duke Scientific Corp. (Palo Alto, CA, USA) were used as standard particles which were dispersed at 0.1%(w/v) in the carrier liquid.…”
Section: 10mentioning
confidence: 99%
“…Field-flow fractionation (FFF) is a separation technique for macromolecules, and can be useful in various fields including biotechnology. [4][5][6] FFF is also well suited to analytical-scale separation and characterization of nano to micron-sized particles. 7,8 FFF has been successfully applied to characterization and separation of colloids with biological interest such as yeast.…”
mentioning
confidence: 99%